Performance of Activated Ricinus Communis Leaves for Degradation Oily Wastewater from Aqueous Solution (Journal of University of Babylon for Engineering Sciences, 2019)
In this work, Ricinus Communis leaves used as adsorbent to eliminate dissolved oil in oil-water emulsion, the adsorbent was used in activated state, the influence of different parameters like initial oil concentration, adsorbent dosage, and contact time were examined in this study. The particle size used was (300 - 150 micron), at (pH < 2), 200 rpm. and adsorbent concentration of 400 mg/L, The oil uptake increased from 78 % to 88% for oil concentration of 2000 mg/L by using natural and activated respectively,  the study was characterized by FTIR, SEM, and BET tests. FTIR test. Activated adsorbent proved good capability of adsorption aliphatic and aromatic hydrocarbons. Isotherm study had used to understand the mechanism of adsorption. Langmuir and Freundlich isotherm were fitted very well  to describe the adsorption resulting by activated adsorbent, this study also characterized by kinetic models, Pseudo second order was the best fitted model for adsorption by adsorbent.